Traumatic Upper and Lower Limb Amputations of Saudi Arabian Locals: A Ten-year Epidemiological Overview (International Journal of Physiotherapy, 2021)
Background: There is a scarcity of understanding about the region-specific trends and relations of amputation-related parameters for Saudi Arabia.Objective: The primary objective of this study was to study the epidemiology of a cross-section of the Saudi Arabian population that has undergone upper or lower limb amputation due to trauma in terms of epidemiological parameters (age, gender, and side of amputation) in the past ten years.Methods: Medical records of five tertiary care hospitals of Saudi Arabia were retrieved to collect data.Results: Data of 245 amputees was analyzed (age: 28.04 ± 23.31 years), out of which 71.42% were male (male: female = 5:2). The frequency of amputations in five tertiary care hospitals in Saudi Arabia was inversely related to the amputees' age group. No significant relationship of gender was found with the level of amputation. However, a significant relationship was found between annual distribution and level of amputation (p = 0.036).Conclusion: Year of amputation had a significant relationship with the level of amputation. Further studies can categorize these amputations according to trauma type to further explore the relationship between demographic parameters andamputation level.